1998
DOI: 10.1099/0022-1317-79-5-1289
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and genome organization of grapevine leafroll-associated virus-2 are similar to beet yellows virus, the closterovirus type member.

Abstract: The entire genome of grapevine leafroll-associated closterovirus-2 (GLRaV-2), except the exact 5h terminus, was cloned and sequenced. The sequence encompasses nine open reading frames (ORFs) which include, in the 5h to 3h direction, an incomplete ORF1a encoding a putative viral polyprotein and eight ORFs that encode proteins of 52 kDa (ORF1b), 6 kDa (ORF2), 65 kDa (ORF3), 63 kDa (ORF4), 25 kDa (ORF5), 22 kDa (ORF6), 19 kDa (ORF7) and 24 kDa (ORF8) respectively, and 216 nucleotides of the 3h untranslated region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 27 publications
(36 reference statements)
2
58
0
1
Order By: Relevance
“…The Closteroviridae hallmark gene array consists of ORFs for a putative small hydrophobic protein (SHP), a heat shock protein homologue (Hsp70h), a protein of 50 to 60 kDa depending on the virus, the CP, and the minor CP (CPm), which are, like most proteins in Closteroviridae, translated from subgenomic RNAs (sgRNAs) (2,20,24,30,33,34,37,41,43,65). The genomic sequence of SPCSV is unknown except for partial sequences of Hsp70h and CP gene sequences from a few isolates (4,28,61).…”
mentioning
confidence: 99%
“…The Closteroviridae hallmark gene array consists of ORFs for a putative small hydrophobic protein (SHP), a heat shock protein homologue (Hsp70h), a protein of 50 to 60 kDa depending on the virus, the CP, and the minor CP (CPm), which are, like most proteins in Closteroviridae, translated from subgenomic RNAs (sgRNAs) (2,20,24,30,33,34,37,41,43,65). The genomic sequence of SPCSV is unknown except for partial sequences of Hsp70h and CP gene sequences from a few isolates (4,28,61).…”
mentioning
confidence: 99%
“…The AFM analyses revealed that the tail is thinner than the rest of the virion and that it is subdivided into three segments. Very similar tail morphology was observed for a BYV relative, grapevine leafroll-associated virus 2 (35) (Fig. 7, which is published as supporting information on the PNAS web site), indicating that the tail structure is conserved at least among two members of the genus Closterovirus.…”
Section: Discussionmentioning
confidence: 50%
“…These included development of rapid serological detection of viruses infecting a range of plants, including woody plants (62), vegetables (51), and others such as cardamom (28); development of pseudorecombinants of multicomponent viruses (6, 32); and cross-protection studies on zucchini yellow mosaic (55), tomato ringspot (2), and tomato spotted wilt (57) viruses. Later work led to development and testing of virus-resistant transgenic vegetables (12-14, 22, 58); some work on the mechanism of transgenic virus resistance (40)(41)(42); sequencing of viral genomes (33,38,63); and risk assessment studies of virus-resistant transgenic plants (11). I also did a lot of international work on a range of viruses, which helped to attract numerous graduate students, postdoctoral associates, and scientists to my laboratory.…”
Section: Synopsis Of My Research Effortsmentioning
confidence: 99%